Heat efflux estimation during a borehole drilling - Vladimir I. Zui; Yaroslav G. Gribik; Aleksandr L. Suslenko (Журнал Белорусского государственного университета: География, геология, 2017)
A field experiment to estimate the withdrawal of heat by a circulating mud was described on the basis of the borehole «Novo-Korenevskaya-13» located within the Pripyat Trough (Belarus) which was in a drilling process. A rock fragmentation process is accompanied by a heat release. Drilling of deep wells is fulfilled using a drilling mud (usually a clay mud). It cools the tool which frays and crushes rocks at the well bottom as well as removes detritus from a wellbore to the ground surface. The paper is devoted to calculation of the heat efflux by circulating drilling fluid during this well drilling. It was shown that this mud, circulating along the wellbore, evacuates to the ground surface not only detritus but provides the heat efflux as well. The experiment included the temperature monitoring of the drilling mud pumped into a drill string and its outflow from the well. We discuss the heat power delivered to the ground surface. It was confirmed that the heat efflux by the circulating fluid in a wellbore could attain hundreds of kilowatts or even slightly exceed 1 MWth depending on the drilling depth, drillable rock types and the natural rock temperature at the considered depth. An assessment of heat withdrawal in the process of deep borehole drilling during oil exploration works within the Pripyat Trough represents both a scientific and practical interest. The heat release during the drilling process could be used for practical purposes.